Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the first three terms of the sequence defined by the function [tex]\( f(n) = -2n + 3 \)[/tex], we start by evaluating the function for the first three values of [tex]\( n \)[/tex].
### Step 1: Calculate the First Term ([tex]\( n = 1 \)[/tex])
For [tex]\( n = 1 \)[/tex]:
[tex]\[ f(1) = -2(1) + 3 \][/tex]
Perform the multiplication:
[tex]\[ -2 \cdot 1 = -2 \][/tex]
Then add 3 to -2:
[tex]\[ f(1) = -2 + 3 = 1 \][/tex]
So, the first term is [tex]\( 1 \)[/tex].
### Step 2: Calculate the Second Term ([tex]\( n = 2 \)[/tex])
For [tex]\( n = 2 \)[/tex]:
[tex]\[ f(2) = -2(2) + 3 \][/tex]
Perform the multiplication:
[tex]\[ -2 \cdot 2 = -4 \][/tex]
Then add 3 to -4:
[tex]\[ f(2) = -4 + 3 = -1 \][/tex]
So, the second term is [tex]\( -1 \)[/tex].
### Step 3: Calculate the Third Term ([tex]\( n = 3 \)[/tex])
For [tex]\( n = 3 \)[/tex]:
[tex]\[ f(3) = -2(3) + 3 \][/tex]
Perform the multiplication:
[tex]\[ -2 \cdot 3 = -6 \][/tex]
Then add 3 to -6:
[tex]\[ f(3) = -6 + 3 = -3 \][/tex]
So, the third term is [tex]\( -3 \)[/tex].
### Final Answer
The first three terms of the sequence are:
[tex]\[ 1, -1, -3 \][/tex]
Thus, the first three terms of the sequence defined by [tex]\( f(n) = -2n + 3 \)[/tex] are [tex]\( 1 \)[/tex], [tex]\( -1 \)[/tex], and [tex]\( -3 \)[/tex].
### Step 1: Calculate the First Term ([tex]\( n = 1 \)[/tex])
For [tex]\( n = 1 \)[/tex]:
[tex]\[ f(1) = -2(1) + 3 \][/tex]
Perform the multiplication:
[tex]\[ -2 \cdot 1 = -2 \][/tex]
Then add 3 to -2:
[tex]\[ f(1) = -2 + 3 = 1 \][/tex]
So, the first term is [tex]\( 1 \)[/tex].
### Step 2: Calculate the Second Term ([tex]\( n = 2 \)[/tex])
For [tex]\( n = 2 \)[/tex]:
[tex]\[ f(2) = -2(2) + 3 \][/tex]
Perform the multiplication:
[tex]\[ -2 \cdot 2 = -4 \][/tex]
Then add 3 to -4:
[tex]\[ f(2) = -4 + 3 = -1 \][/tex]
So, the second term is [tex]\( -1 \)[/tex].
### Step 3: Calculate the Third Term ([tex]\( n = 3 \)[/tex])
For [tex]\( n = 3 \)[/tex]:
[tex]\[ f(3) = -2(3) + 3 \][/tex]
Perform the multiplication:
[tex]\[ -2 \cdot 3 = -6 \][/tex]
Then add 3 to -6:
[tex]\[ f(3) = -6 + 3 = -3 \][/tex]
So, the third term is [tex]\( -3 \)[/tex].
### Final Answer
The first three terms of the sequence are:
[tex]\[ 1, -1, -3 \][/tex]
Thus, the first three terms of the sequence defined by [tex]\( f(n) = -2n + 3 \)[/tex] are [tex]\( 1 \)[/tex], [tex]\( -1 \)[/tex], and [tex]\( -3 \)[/tex].
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.